The construction ground of political stability in North Africa : The Arab Maghreb Union - Hadji, Brahim (My University, 2023)
Çalışma, Kuzey Afrika ülkeleri için bölgesel bir entegrasyon bloğu olarak Arap Mağrip Birliği içindeki zayıflığın nedenlerini ortaya koymaktadır. Bu araştırma, bölgesel entegrasyonlar için ideasyon ve norm faktörlerine daha fazla vurgu yapan yapılandırmacılık teorisine dayanmaktadır. Çalışma esnasında araştırmacı, problemleri nedensel mekanizma sürecini vurgulamak ve bu nedenselliği kontrol eden müdahale değişkenlerini belirlemeyi en uygun yöntem olarak süreç izleme metodolojisini benimsemiştir. Başlıca bulgular, kolektif kimliğin yokluğuna işaret etmektedir; Batı Sahra ile ilgili çatışmacı fikirler, ekonomik karşılıklı bağımlılığın önünü açan anlaşmaların olmaması, ekonomik anlayışın dış paylaşımı ve Arap Mağrip Birliği bölgesinde toplu güvenlik eksikliği gibi nedenler bloğu önemli ölçüde zayıflatmaktadır. Araştırma bulguları, Arap Mağrip Birliği'ne üye ülkelerin sağlam bir bölgesel entegrasyon inşa etmek için ortak siyasi, ekonomik ve güvenlik fikirlerini ve normlarını benimsemelerini tavsiye etmektedir.

The study illustrates the causes of the weakness within the Arab Maghreb Union as a regional integration block for the North African countries. This research is constructed through the constructivism theory, which emphasizes ideational and norm factors for regional integrations. During this study, the researcher adopts process-tracing methodology as the most suitable methodology to emphasize the causal mechanism process of research problems as well as to identify the intervention variables that control this causality. The major findings of this study indicate the absence of collective identity, the conflicting ideas regarding Western Sahara, the absence of mutual understandings of economic interdependence, the external shared understandings of economy, and the absence of collective security within the Arab Maghreb Union region that make the block very weak. Based on the study findings, the research recommends that member countries of the Arab Maghreb Union should embrace shared political, economic, and security ideas and norms to construct solid regional integration.
Kuzey Afrika'da siyasi istikrarın inşası : Arap Mağrip Birliği
Keywords: ABSTRACT; and the absence of collective security within the Arab Maghreb Union region make the block very weak; Arap Mağrip Birliği; Basing on the study findings; Bölgesel Entegrasyon; During this study; History; Konstrüktivizm teorisi; Maghreb; Mağrip; Major findings of this study indicates the absence of collective identity; Süreç İzleme Metodolojisi; Tarih; the absence of mutual understandings on economic interdependence; the conflicting ideas regarding the Western Sahara; The Construction Ground of Political Stability in North Africa: The Arab Maghreb Union; the external sharing of economic understanding; the research recommends that member countries of the Arab Maghreb Union should embrace sharing ideas and norms in order to construct solid regional integration; the researcher adopted process-tracing methodology as the most suitable methodology to emphasize the causal mechanism process of research problems as well as to identify the intervention variables that control these causality; The study illustrates the causes for the weakness within the Arab Maghreb Union as a regional integration block for the North African countries; This research is enshrined into the constructivism theory that emphasizes more on ideation and norms factors for regional integrations